Porozumienie miedzy pokoleniami w rodzinie - płaszczyzny rozwoju - Kozubska, Alicja (Karkonoska Państwowa Szkoła Wyższa, 2011)
Reaching agreement among generations in a family is crucial for its proper functioning. Children, parents and grandparents may enrich their lives through exchanging many values (mentioned in the text). Dialogue between generations is equally important and precious for all generations within an extended family. Moreover, the dialogue creates a feeling of closeness, protects against alienation and provides generations with cultural continuity. However, reaching agreement among generations requires putting a lot of effort from all family members and involves making many mistakes.
Keywords: rodzina; dzieci; rodzice; dziadkowie